« On n’est évidemment pas forcé de tout dire » - Marion Demonteil (Revue d'anthropologie des connaissances)
This article aims at showing the contributions of an approach in terms of ignorance for the sociology of administration. Starting from the case of inspectorates’ reports, it reverses the classical terms of the study of reports, which emphasize the knowledge produced as a tool of government, and is based on the hypothesis that this grey literature contributes to maintaining the established order less by what it reveals than by what it conceals. Following the career of the inspectorates’ reports, it highlights the everyday and pre-reflexive forms that characterize inspectoral production as well as its institutional conditions of possibility. By articulating a micro-ignorance and a macro-ignorance, the demonstration contributes to the analysis of the institutional virtues of unknowing.